Analysis and determination of tofu production risk mitigation strategy using FMEA and AHP methods (Case study: UD XYZ) - Anisa Dwi Aryani; Wahyuda Wahyuda; Suwardi Gunawan (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2022)
In the tofu production process, UD XYZ is inseparable from the risks that may occur so that it can interfere with tofu production activities. Therefore, to handle the existing risks, it is necessary to carry out risk management by mitigating risks. Data collection techniques used are secondary data and primary data. The data processing technique and data analysis used the Failure Mode Effect Analysis (FMEA) method and the Analytical Hierarchy Process (AHP) method. The results of data processing using the FMEA method are known to be risk factors for raw materials with the highest RPN value, namely the risk of poor soybean quality with an RPN value of 720, the risk factor for the highest RPN production process is the risk of the dose of supporting raw materials not in accordance with the RPN value of 320, and the highest RPN finished product risk factor is the risk of damaged tofu when packaged with an RPN value of 36. The results of data processing using the AHP method with the help of Benefit, Cost, Opportunities, and Risk (BCOR) criteria are known that the criteria with values the highest is the benefit criteria with a value of 0.600. In the risk of raw materials, namely the quality of soybeans is not good, it is known that the chosen alternative strategy is to use the best raw material supplier with a value of 0.738. In the risk of the production process, namely the dose of supporting raw materials is not appropriate, it is known that the chosen alternative strategy is to make a Standard Operating Procedure (SOP) with a value of 0.671. The existence of SOPs will help to achieve goals because of the design that guides employees in carrying out their duties and to minimize errors when carrying out their respective tasks. Dalam proses produksi tahu, UD XYZ tidak terlepas dari risiko-risiko yang mungkin terjadi sehingga dapat mengganggu aktivitas produksi tahu. Oleh karena itu, untuk menangani risiko yang ada maka perlu dilakukan manajemen risiko dengan memitigasi risiko. Teknik pengumpulan data yang digunakan adalah data sekunder dan data primer. Teknik pengolahan data dan analisis data menggunakan metode Failure Mode Effect Analysis (FMEA) dan metode Analytical Hierarchy Process (AHP). Hasil pengolahan data menggunakan metode FMEA diketahui pada faktor risiko bahan baku risiko dengan nilai RPN tertinggi yaitu pada risiko kualitas kedelai tidak baik dengan nilai RPN sebesar 720, pada faktor risiko proses produksi RPN tertinggi yaitu pada risiko takaran bahan baku pendukung tidak sesuai dengan nilai RPN sebesar 320, dan pada faktor risiko produk jadi RPN tertinggi yaitu pada risiko tahu rusak saat dikemas dengan nilai RPN sebesar 36. Hasil pengolahan data menggunakan metode AHP dengan bantuan kriteria Benefit, Cost, Opportunities, dan Risk (BCOR) diketahui bahwa kriteria dengan nilai-nilai tertinggi yaitu pada kriteria benefit dengan nilai 0.600. Pada risiko bahan baku yaitu kualitas kedelai tidak baik, diketahui bahwa alternatif strategi terpilih adalah menggunakan supplier bahan baku terbaik dengan nilai 0.738. Pada risiko proses produksi yaitu takaran bahan baku pendukung tidak sesuai, diketahui bahwa alternatif strategi terpilih adalah membuat Standar Operasional Prosedur (SOP) dengan nilai 0.671. Dengan adanya SOP dan pemilihan supplier bahan baku terbaik akan membantu memitigasi risiko prioritas sehingga risiko tersebut dapat dikendalikan dan frekuensinya berkurang.